Strategy Management Analysis in Carrying out VLR by BAPPEDA Lampung Province in Efforts to Report SDGs Achievements - Rama Editya Gustomo; Wenny Permata Sari (Riviera Publishing, 2024)
The strategy of a business organization or company involves directing the organization's efforts in utilizing the environment and managing the company's internal capabilities to achieve the desired goals and objectives. This research aims to evaluate and develop management strategies implemented by the Regional Development Planning Agency (BAPPEDA) of Lampung Province in conducting Voluntary Local Review (VLR) to report the achievement of SDGs in Lampung province. The type of research used is qualitative with informants in this study, namely the head of government planning and human development (1 person), young expert planning staff (2 people), and Lampung Province SDGs secretariat staff (2 people). This research seeks to provide an in-depth understanding of the factors that influence the success of the VLR, as well as the opportunities and challenges faced in achieving SDGs targets at the regional level. The originality of the research lies in the application of Soft System Methodology (SSM) as a systemic approach in the context of SDGs reporting at the provincial level and contributes to the understanding of strategic management in supporting sustainable development. Research using Soft System Methodology (SSM) on Lampung Province Bappeda's strategy in implementing Voluntary Local Review (VLR) of SDGs achievements resulted in recommendations, including increased coordination, management capacity, data quality, actor empowerment, and transparency and accountability.